Organic plant ingredients in the diet of Rainbow trout (Oncorhynchus mykiss): Impact on fish muscle composition and oxidative stability. Issue 12 (20th November 2013) - Baron, Caroline P.; Svendsen, Gry Hougaard; Lund, Ivar; Jokumsen, Alfred; Nielsen, Henrik Hauch; Jacobsen, Charlotte
<x xml:space="preserve">Abstract</x> Rainbow trout were fed diets containing either fish meal and fish oil (FM‐FO) (control) or diets in which 40% of the fishmeal was substituted with a mixture of ingredients grown organically including plant protein concentrate (PP) in combination with either fish oil (FO) as lipid source, or one of the following organic plant oils; rapeseed (RO), linseed/flaxseed (LO), grape seed (GO), or sunflower (SO). The impact of these substitutions was investigated by measuring fish muscle fatty acid profile as well as oxidative and color stability of the fillet during 14 days ice storage. The inclusion of plant protein concentrate did not affect the fatty acid profile significantly but resulted in a slightly improved oxidative stability of the fish fillets as compared to the control diet. The fatty acid profile of the oil used was in general well reflected in the fish muscle fatty acid profile. Fish fed PP‐RO were the most oxidatively stable during ice storage but the omega‐3 fatty acid content was reduced by 40% compared to fish fed the FM‐FO control diet. Replacing FO by LO was not suitable as it induced oxidation and the fillet contained 40–50% less of long chain omega‐3 fatty acids. Practical applications: Replacing marine ingredient by organic plant ones in the diet of rainbow trout is feasible but it impacts the fish fatty acid profile of the fish muscle and its oxidative stability. Plant protein improved the oxidative stability of the fillet during ice storage. Moreover, replacement of fish oil with more saturated plant oils in the diet of trout lead to an increased oxidative stability of the fillet, but at the same time reduced the level of omega‐3 fatty acids in the fish muscle. Linseed oil resulted in a more favorable omega‐3 content (ALA) than the other plant oils but resulted in highly unstable fish muscle with respect to oxidation. Substitution of fish ingredients in the fish diet significantly influenced the nutritional value of the fish fillet, as it resulted in significant less EPA and DHA in the muscle.